Medical Skills in a Clinical Presentation-Based Curriculum: Approach to the Patient With Shoulder Pain - Gordon Woods; Justin Wright (Association of American Medical Colleges, 2014)
Abstract The material in this resource guide is for clinical faculty as they organize and present a learning session for preclerkship medical students on the clinical workup of shoulder pain. During the session, students individually (or in pairs) work through the interview and perform the examination of a standardized patient presenting with shoulder pain. After this encounter, students write a subjective, objective, assessment, plan note, receive feedback from the standardized patient (and from their peer observer, if present), and debrief in a group discussion with a faculty member. The session includes a readiness assurance quiz, preparatory exam room guide with video, summary outline that students can use during the standardized patient encounter, a check sheet to guide peer observer feedback, and a standardized patient case blueprint. This material would be of interest to preclerkship clinical skills instructors who would like to teach their trainees a structured history and physical exam that they can immediately apply in their clinical activities. This material was originally developed for the Medical Skills Course at the Texas Tech University Paul L. Foster School of Medicine (PLFSOM) in El Paso, Texas. The pre-clerkship curriculum at the PLFSOM is a fully integrated, clinical presentation-based curriculum. This curricular structure allows clinical skills instruction to be tightly integrated with basic science content. Therefore, it is important to situate this session in the curriculum after relevant basic science content has been covered. The case of the patient with shoulder pain is a good platform for building a basic set of musculoskeletal exam skills. History taking is structured around three categories of pathology that commonly affect the musculoskeletal system. This simplifies the workup and decreases the problem of information overload which can easily occur when teaching musculoskeletal medicine.